False Identity dalam Media Online Dating (Fenomenologi pada Pelaku Catfishing Media Online Dating Tinder) - Rifai Septian Nurdin (Mahesa Research Center, 2021)
This study aims to determine the process of a person's interaction on Tinder social media, causing a new phenomenon known as catfishing. This research uses a qualitative approach. The data collection technique was obtained by using in-depth interview techniques. The results of the study show that the self-presentations displayed by Tinder users are not using their real photos or identities. The scope of self-presentation shown in this study does not extend to false identity or paint through identity theft. Tinder users in this study tended to use their original photos that they had edited to look better and closer to the ideal Tinder users liked, use their old photos that were considered better and closer to ideal, blur their original photos, use their real photos but not using real names, to using photos of objects or objects that interest them to show their interests and hobbies to other users. In this study, there were no users who used other people's existing identities either by using other people's photos or identities that showed someone who was in real life.